Proceedings of the 42nd ACM Technical Symposium on Computer Science Education 2011
DOI: 10.1145/1953163.1953340
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing CS1 exam question content

Abstract: Many factors have been cited for poor performance of students in CS1. To investigate how assessment mechanisms may impact student performance, nine experienced CS1 instructors reviewed final examinations from a variety of North American institutions. The majority of the exams reviewed were composed predominantly of high-value, integrative codewriting questions, and the reviewers regularly underestimated the number of CS1 concepts required to answer these questions. An evaluation of the content and cognitive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 24 publications
1
47
0
3
Order By: Relevance
“…Using published lists of CS concepts [9,4], Petersen et al [7] investigated the number of concepts embodied in typical CS1 final exam questions. In a sample of fifteen CS1 final exams, the authors found that 59% of exam marks were devoted to code-writing questions.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Using published lists of CS concepts [9,4], Petersen et al [7] investigated the number of concepts embodied in typical CS1 final exam questions. In a sample of fifteen CS1 final exams, the authors found that 59% of exam marks were devoted to code-writing questions.…”
Section: Related Workmentioning
confidence: 99%
“…Writing code is the major determinant of whether a student passes CS1, and the widespread use of integrative codewriting questions [7,11] suggests that CS1 instructors believe they are important assessments of student understanding. We are therefore interested in measuring the extent to which concept questions measure what is measured by writing questions.…”
Section: Predicting Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Santana (2015), após uma análise de várias definições, o Pensamento Computacional pode ser tratado como "o desenvolvimento de habilidades que favorecem a resolução de problemas, em que através da organização do modo de pensar, é possível expandir a capacidade mental, permitindo resolver os mais diversos níveis de desafio". Porém, programar não é uma tarefa fácil (LAHTINEN; ALA-MUTKA; JÄRVINEN, 2005) e a disciplina introdutória de algoritmos possui altas taxas de reprovação e abandono (PETERSEN; CRAIG; ZINGARO, 2011). Por isso iniciativas como o code.org exploram o ensino com crianças e adolescentes e estimulam as habilidades necessárias para auxiliar iniciantes em programação introdutória.…”
Section: Introductionunclassified
“…However, PI focuses on in-class discussions of multiple-choice questions, and such a focus suggests a mismatch between PI and the skill-based practice required of CS1 students. Many of the skills typically expected of CS1 students relate to code-investigation and code-writing [5], and code-writing is disproportionately used to gauge student skill on final exams [12].…”
Section: Introductionmentioning
confidence: 99%